The value of local association in Muslim society religious culture in Silau Laut Asahan district - Siagian, Nilasari (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study was to determine the value of local wisdom in the religious culture of the Muslim community in Glare Laut Sub-District, Asahan District, Silas Laut District. The type of research used is juridical sociological or juridical empirical research, namely legal research that examines law as a social phenomenon using field data as the main data source. The primary data sources used consisted of observations and interviews from data sources or research subjects, namely community members and community leaders. Meanwhile, the data analysis method was carried out through the process of editing, classifying, verifying, analyzing, and concluding. Based on the results of the research it can be concluded that there are several cultures or religious traditions that have been started by Mr. Syeh Abdurrahman Silau and are still being preserved by the Silau Laut community until now, including Totau Negeri or Manotau Kampong, Forest of Prohibition, Eating Rambong Chicken (Closing Bondang and Buka Bondang), and the Memoncak tradition. These various cultures have then become living laws and are local wisdom values that are continuously maintained and preserved by the people of Silau Laut, especially in the village of Silau Lama. Furthermore, when viewed from the aspect of Islamic Law, various cultures or religious traditions that have been started by Mr. Syeh Abdurrahman Silau and are still being preserved by the Silau Laut community until now can be categorized as' urf shahihah.